Health-related lifestyle behaviours and healthcare utilisation among adolescent immigrants in Europe - Krzysztof Czaderny (Comparative Migration Studies)
Abstract The healthy immigrant paradox suggests that immigrants tend to have better health than native residents, despite facing socio-economic disadvantages. At the same time, immigrants are considered to utilise healthcare less. This study compares health-related lifestyle behaviours and healthcare utilisation between foreign-born and native-born adolescents living in Europe. It uses the partial least squares method and data from the 2019 European Health Interview Survey, covering 15,320 individuals aged 15–19 years. On average, being foreign-born was positively associated with following a healthy diet, engaging in physical activity, avoiding smoking, and avoiding alcohol. However, these relationships largely varied depending on whether the adolescents originated from within or outside the European Union. Conversely, being foreign-born was generally linked to lower healthcare utilisation. The utilisation of healthcare was by far the lowest among adolescents born outside the European Union who were not citizens of a European Union member state, which contrasts with health-related lifestyle behaviours. Furthermore, the association between being in this group and healthcare utilisation was moderated by equivalised household income. This aligns with previous research suggesting that immigrants tend to underutilise healthcare, primarily due to administrative and economic barriers. Unlike foreign-born adolescents, second-generation immigrants did not differ significantly from their native counterparts in most health-related behaviours analysed. In conclusion, promoting selective acculturation among adolescent immigrants and enhancing their access to healthcare is recommended.